FILM AS CULTURAL DIPLOMATION ASSETS - Suryanto, Hari; Amri, Mariani (Capture : Jurnal Seni Media Rekam, 2018)
Indonesia's cultural wealth is one of the potential strengths to create harmony and the formation of national character. Cultural diffusion through diplomacy is a way that can build a good dialogue about the worthy values in culture to a wider society. The film consists of two elements, namely, the narrative element as a story builder framed in a theme to sharpen the story message. And cinematic elements that provide audio-visual support clearly and more detailed. The ability of films for diplomacy purposes in communicating the cultural values of this nation has no doubt. Film is a combination of various fields of art that flows unity in one and is supported by technology so that the film has the ability to be an effective medium of communication in the current era.